QUALITY ASSESSMENT OF EDIBLE TOMATO VARIETIES INTENDED FOR INDUSTRIAL PROCESSING - Mendelová, Andrea; Fikselová, Martina; Mendel, Ľubomír; Andrejiová, Alena; Mareček, Ján; Czako, Peter (Journal of microbiology, biotechnology and food sciences, 2015)
Most of the global production of tomatoes is used for tomato products. The fruits to be processed are evaluated on the basis of important technological quality parameters, such as the content of dry matter and organic acids. Recently, among important qualitative characteristics of fruits has been included colorant content, especially lycopene. Aim of this study was to evaluate the quality of selected tomato varieties for industrial processing. Tested were varieties Uno Rosso, San Marzano 4, Brixol, Strombolino, UG. 8168, Diana and Nemarock cultivated in very hot and dry agro-climatic region. The dry matter content was determined by the gravimetric method, the content of organic acid by titration and the content of colorants spectrophotometrically. The dry matter content of the samples ranged from 4.65% (Nemarock) to 5.93% (San Marzano 4). Content of organic acids ranged from 0.33% (Nemarock) to 0.59% (Strombolino), content of carotenoids in tomato samples ranged from 111.288 mg.100 g-1 DM (Nemarock) to 198.365 mg.100 g-1 DM (San Marzano 4). Lycopene was present in the amount of 99.438 mg.100 g-1 DM (Nemarock) to 192.687 mg.100 g-1 DM (San Marzano 4). In terms of treatment the best properties showed San Marzano 4, which is characterized by high dry matter content, low organic acids and high content of colorants.